Re-bleeding and all-cause mortality risk in non-variceal upper gastrointestinal bleeding: focusing on patients receiving oral anticoagulant therapy - Won Shik Kim; Seung Han Kim; Moon Kyung Joo; Jong-Jae Park; Beom Jae Lee; Hoon Jai Chun (Annals of Medicine, 2023)
AbstractObjective Non-variceal upper gastrointestinal bleeding (NVUGIB) in patients receiving oral anticoagulants (OACs) may be fatal; however, little is known about re-bleeding and all-cause mortality after successful hemostasis. We investigated the clinical characteristics and risk factors for re-bleeding and death after successful hemostasis.Methods Patients receiving OACs and diagnosed with NVUGIB between 2007 and 2021 were enrolled. All NVUGIB incidents were confirmed if definite bleeding in the upper gastrointestinal tract was detected via esophagogastroduodenoscopy.Results A total of 132 patients receiving OACs were diagnosed with NVUGIB. Males were the majority (72, 54.5%), and bleeding was detected mostly in the stomach (99, 75%) and was most often due to peptic ulcers (PU) (88, 66.7%). After successful hemostasis of index NVUGIB, 40 patients (30.3%) experienced re-bleeding. Among them, 15 (37.5%) died, and among those, 3 (2.3%) were related to re-bleeding. Multivariate analysis revealed that duodenal bleeding (odds ratio [OR]: 3.305; 95% confidence interval [CI]: 1.152-9.479, p = 0.026) and Charlson comorbidity index score (CCI) (OR: 1.22; 95% CI: 1.052–1.419, p = 0.009) were significant risk factors for re-bleeding. Index albumin levels (OR: 0.134; 95% CI: 0.035–0.506, p = 0.003), previous PU or upper gastrointestinal bleeding (UGIB) history (OR: 4.626; 95% CI: 1.375–15.567, p = 0.013), and CCI (OR: 1.293; 95% CI: 1.058–1.581, p = 0.012) were related all-cause mortality.Conclusion CCI and duodenal bleeding are risk factors for re-bleeding in patients with NVUGIB who were receiving OACs, while low index albumin levels and previous PU and UGIB history are associated with all-cause mortality.